Preferensi Pelanggan terhadap Pasar Online: Studi Kasus Marketplace Shopee - Rosseh, Akbar; Pasaribu, Popy Novita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Then the charm of the Shopee Marketplace by using Google distribution from for 1 (one) week, the researcher obtained 97 respondents but those studied by researchers who were only included in the criteria for selecting Shopee products, then excluding 9 respondents who did not choose Shopee products, so only 88 respondents processed with SPSS Multiple regression, all variables remembered Y1, Y2, Y3 were tested one by one with the independent variables X1, X2, X3, X4, X5, X6, X7, so the categories related to the limbic map, the researcher took the three largest Shopee marketplace customer values ​​are family, success and discipline. The family frequency of 91.8% in one family shows that they tend to shop online because they save money without having to leave the house, the Shopee application has been widely available. Success Value 80.6% the value of branches or comments from customers because they will be taken into consideration when buying. Thus the limbic map type of Shopee marketplace based on Hausel's theory is in Discipline/control. Customer preferences seen from the side of affection are influenced by entertainment, personalization and domain name variables. Customer preferences seen from the side of cognition are influenced by the quality of information, usability and domain names. Meanwhile, customer preference based on conation is 54% interactivity, information quality and usability. Keyword: customers, online market, marketplace Shopee